Mode referencing of an external cavity diode laser for continuous frequency stabilization - WELDON, VINCENT; DONEGAN, JOHN (My University, 2008)
The output of an external cavity diode laser (ECDL) is frequency stabilized to a water (H2O) vapor absorption line at 935 nm using wavelength modulation spectroscopy (WMS) by means of a dual-feedback locking loop. A novel mode-referencing technique is presented that, in conjunction with the feedback locking mechanism, helps improve the overall frequency-locking system. The mode-referencing enables the device output to maintain its locked frequency in the presence of environmental and other effects, which may cause the operational characteristics of the laser to drift.
PUBLISHED
Keywords: mode-referencing; external cavity diode laser; frequency stabilization